STEM in Primary school - between theory and practice - Ivelina Miteva-Belcheva; Mariya Zhelyazkova (Педагогически форум)
This article focuses on STEM education in Primary school as well as ways of applying it during self-studying and special interest activities. A STEM activity for second grade students with a topic ‘Animate and Inanimate Nature’ is given as an example. There are ways to integrate the topic of the activity with the knowledge students have in subjects like Bulgarian Language, Arts and Crafts, and Science. Further ideas on STEM activities are also introduced.